Adiksi Smartphone Ditinjau dari Attachment Orang Tua – Remaja dan Regulasi Emosi - Proborini, Renyep; Septania, Sovi (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
The problem of smartphone addiction which is increasing and has negative impacts cognitively, emotionally and socially, is the background that drives this research. This study aims to examine the effect of parent-adolescent emotional regulation and attachment on smartphone addiction. There are two independent variables, namely emotional regulation and parent-adolescent attachment and one dependent variable, namely smartphone addiction.The study was conducted at SMAN 16 Bandar Lampung, with a sample of 325 students. The sample was selected by the purposive sampling technique. The research method uses quantitative methods. Measurement of smartphone addiction using the SAI or Smartphone Addiction Inventory scale from Lin, attachment using the IPPA (Inventory of Parent and Peer Attachment) scale from Greenberg, and emotion regulation using the Emotion Regulation Questionnaire scale from Gross. There are three research hypotheses, namely (H1): there is an effect of parent-adolescent attachment on smartphone addiction. (H2) there is an effect of emotion regulation on smartphone addiction and (H3) there is an effect of parent-adolescent attachment and emotion regulation on smartphone addiction The results showed that parent-adolescent attachment had a relationship of – 0.231 with smartphone addiction, while emotion regulation was not proven to have a relationship. The two independent variables together have a relationship with smartphone addiction of 0.311 and the magnitude of the influence of 9.6% on smartphone addiction.